Electro-assisted joining of copper alloy / titanium alloy bimetallic heterogeneous structure and preparation method

CN122875736APending Publication Date: 2026-10-09XIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610990133.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-03
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0003]现阶段铜合金/钛合金双金属主要依靠各类熔焊与热等静压工艺制备,其一,各类熔焊工艺难以适配大深径比(>2:1)、细小内孔(≤8mm)的缸体结构,热等静压工艺易造成钛合金缸体变形与尺寸失准,高温还会诱发钛合金β相变,破坏基体原有力学性能;其二,铜与钛固溶度极低,高温连接条件下铜合金/钛合金连接界面处易快速生成大量脆性金属间化合物,造成铜合金/钛合金连接界面的力学性能劣化与接头开裂,难以满足航空构件的使用要求

Benefits of technology

第一方面,本发明提供了一种电辅助连接铜合金/钛合金的双金属异质结构的制备方法,通过控制直流电的电流路径先沿表面活化的钛合金缸体外围传导,利用预压实铜合金粉块在致密化前后的电阻动态变化,待预压实铜合金粉块致密化后使电流路径自动反转至优先穿过致密化后的预压实铜合金粉块,形成选择性内热聚焦,能够适配大深径比(>2:1)、细小内孔(≤8mm)的缸体结构,避免钛合金缸体因局部过热而发生变形。同时,电流路径转换机制有效抑制了铜合金/钛合金连接界面处过量脆性金属间化合物的生成,改善了铜合金/钛合金连接界面的结合质量。另外,通过配合石墨压头实现热压烧结过程中的力场与电场协同作用,使预压实铜合金粉块在低热载荷下充分致密化并与钛合金缸体的内孔壁形成可靠冶金结合。本方法解决了现有技术难以适配大深径比、细小内孔缸体结构,易造成钛合金缸体变形,且铜合金/钛合金连接界面处易生成过量脆性金属间化合物的问题,显著提升了双金属异质结构的连接可靠性与界面性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875736A_ABST
    Figure CN122875736A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of metal processing, and discloses a double-metal heterogeneous structure of electrically assisted copper alloy / titanium alloy connection and a preparation method thereof. The preparation method comprises the following steps: sequentially placing pre-compacted copper alloy powder blocks and a graphite pressure head into an inner hole of a surface-activated titanium alloy cylinder body to obtain an assembly; and performing hot-pressing sintering on the assembly through direct current to obtain the double-metal heterogeneous structure. The current path of the direct current firstly conducts along the periphery of the surface-activated titanium alloy cylinder body, and reverses to preferentially pass through the pre-compacted copper alloy powder blocks after the pre-compacted copper alloy powder blocks are densified. The application can adapt to cylinder body structures with large depth-diameter ratios and small inner holes, avoid deformation of the titanium alloy cylinder body due to local overheating, and effectively inhibit the generation of excessive brittle intermetallic compounds at the copper alloy / titanium alloy connection interface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal processing technology, specifically to an electrically assisted bimetallic heterostructure for connecting copper alloys / titanium alloys and its preparation method. Background Technology

[0002] Copper alloys possess excellent thermal and electrical conductivity as well as wear resistance, while titanium alloys exhibit superior specific strength. The copper / titanium alloy bimetallic components prepared by combining the two can achieve complementary performance and have broad application prospects in fields such as aerospace hydraulic components and marine equipment. Using titanium alloys to replace traditional alloy steel in the preparation of hydraulic cylinders can significantly reduce the weight of components and effectively improve the maneuverability of aircraft.

[0003] Currently, copper / titanium bimetallic alloys are mainly prepared using various fusion welding and hot isostatic pressing processes. However, these processes are not suitable for cylinder structures with large aspect ratios (>2:1) and small internal diameters (≤8mm). Hot isostatic pressing can easily cause deformation and dimensional inaccuracies in the titanium alloy cylinder, and high temperatures can also induce β-phase transformation in titanium alloys, damaging the original mechanical properties of the matrix. Secondly, copper and titanium have extremely low solid solubility. Under high-temperature joining conditions, a large number of brittle intermetallic compounds can quickly form at the copper / titanium alloy interface, causing deterioration of the mechanical properties of the copper / titanium alloy interface and joint cracking, which makes it difficult to meet the requirements for use in aerospace components.

[0004] Therefore, existing technologies are difficult to adapt to cylinder block structures with large depth-to-diameter ratios and small inner bores. This not only easily causes deformation of titanium alloy cylinder blocks, but also generates excessive brittle intermetallic compounds at the copper alloy / titanium alloy interface. These technical problems urgently need to be solved. Summary of the Invention

[0005] The purpose of this invention is to provide an electrically assisted bimetallic heterostructure for connecting copper alloys and titanium alloys and its preparation method, so as to overcome the problems existing in the prior art. This invention can be adapted to cylinder structures with large aspect ratios and small inner holes, avoid deformation of titanium alloy cylinders due to local overheating, and effectively suppress the formation of excessive brittle intermetallic compounds at the copper alloy / titanium alloy connection interface, thereby improving the bonding quality of the copper alloy / titanium alloy connection interface.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a method for preparing an electrically assisted bimetallic heterostructure of copper alloy / titanium alloy, comprising the following steps: Pre-compacted copper alloy powder blocks and graphite indenters are sequentially placed into the inner hole of a surface-activated titanium alloy cylinder to obtain an assembly. The assembled components are hot-pressed and sintered using direct current to obtain a bimetallic heterostructure; wherein the current path of the direct current satisfies: The DC current path is first conducted along the periphery of the surface-activated titanium alloy cylinder. After the pre-compacted copper alloy powder is densified, the DC current path is reversed to preferentially pass through the densified pre-compacted copper alloy powder.

[0007] In some embodiments, the preparation step of the surface-activated titanium alloy cylinder specifically includes: The surfaces of the titanium alloy cylinder to be joined are sequentially machined, washed, subjected to initial ultrasonic cleaning, dried, pickled, and subjected to secondary ultrasonic cleaning to obtain a surface-activated titanium alloy cylinder. After machining, the surface roughness of the titanium alloy cylinder block to be connected is Ra 0.4-1.6 μm.

[0008] In some embodiments, the step of sequentially placing the pre-compacted copper alloy powder block and the graphite indenter into the inner hole of the surface-activated titanium alloy cylinder to obtain the assembly specifically includes: Copper alloy powder is filled into an isostatic pressing sleeve and subjected to cold isostatic pressing pretreatment to obtain pre-compacted copper alloy powder blocks. The pre-compacted copper alloy powder blocks are placed into the inner hole of a surface-activated titanium alloy cylinder to obtain a titanium alloy cylinder containing copper alloy powder blocks. A graphite indenter is pressed into the inner hole of the titanium alloy cylinder containing copper alloy powder blocks to obtain an assembly.

[0009] In some embodiments, the median particle size of the copper alloy powder is 45-70µm, and the flowability of the copper alloy powder is 14-18s / 50g. The pressure of the cold isostatic pressing pretreatment is 100-160MPa, and the holding time of the cold isostatic pressing pretreatment is 2-5min; The graphite indenter is either a cylindrical graphite indenter or a conical graphite indenter, with the conical graphite indenter having a taper of 4-7°.

[0010] In some embodiments, the step of sequentially placing the pre-compacted copper alloy powder block and the graphite indenter into the inner hole of the surface-activated titanium alloy cylinder to obtain the assembly specifically includes: An intermediate layer is prepared on the inner hole of the titanium alloy cylinder body to be connected by an electrodeposition process, resulting in a titanium alloy cylinder body with an intermediate layer. The pre-compacted copper alloy powder block and the graphite pressure head are sequentially placed into the inner hole of the titanium alloy cylinder with the intermediate layer to obtain the assembly. The thickness of the intermediate layer is 10-20µm, and the intermediate layer is a silver layer or a nickel layer.

[0011] In some embodiments, the hot pressing sintering of the assembly using direct current specifically includes: The assembly is placed in a DC-assisted hot press furnace, so that the temperature measuring end of the thermocouple contacts the outer surface of the activated titanium alloy cylinder. Then, mechanical pressure is applied under vacuum, and DC current is turned on for hot pressing sintering. Then, cooling, pressure unloading and furnace cooling are performed in sequence.

[0012] In some embodiments, the temperature after cooling is 300°C, and the pressure unloading rate is 1 MPa / min.

[0013] In some embodiments, the hot pressing sintering includes a first stage and a second stage performed sequentially; The first stage includes: using pre-compacted copper alloy powder blocks to conduct DC current along the periphery of the surface-activated titanium alloy cylinder, heating to 500-550℃ at a rate of 30-80℃ / min and holding at that temperature for 5-10 min. The second stage includes: heating to 650-700℃ at a rate of 10-20℃ / min and holding at that temperature and pressure for 5-30 minutes. After the pre-compacted copper alloy powder is densified, the current path of the DC power is reversed to preferentially pass through the densified pre-compacted copper alloy powder.

[0014] In some embodiments, the pressure of the hot pressing sintering is 15-30 MPa.

[0015] Secondly, the present invention provides an electrically assisted bimetallic heterostructure for connecting copper alloy / titanium alloy, which is obtained by the above-described method for preparing an electrically assisted bimetallic heterostructure for connecting copper alloy / titanium alloy.

[0016] The above technical solution has the following advantages or beneficial effects: Firstly, this invention provides a method for preparing an electrically assisted bimetallic heterostructure of copper alloy / titanium alloy. By controlling the direct current path to initially conduct along the periphery of a surface-activated titanium alloy cylinder, and utilizing the dynamic resistance changes of pre-compacted copper alloy powder before and after densification, the current path automatically reverses after the pre-compacted copper alloy powder is densified, preferentially passing through the densified pre-compacted copper alloy powder. This forms selective internal heat focusing, adaptable to cylinder structures with large aspect ratios (>2:1) and small internal holes (≤8mm), preventing deformation of the titanium alloy cylinder due to localized overheating. Simultaneously, the current path conversion mechanism effectively suppresses the formation of excessive brittle intermetallic compounds at the copper alloy / titanium alloy interface, improving the bonding quality of the interface. Furthermore, by using a graphite indenter to achieve the synergistic effect of force and electric fields during hot-pressing sintering, the pre-compacted copper alloy powder is fully densified under low thermal load, forming a reliable metallurgical bond with the inner wall of the titanium alloy cylinder. This method solves the problems of existing technologies being difficult to adapt to cylinder structures with large depth-to-diameter ratios and small inner bores, which easily cause deformation of titanium alloy cylinders, and the easy formation of excessive brittle intermetallic compounds at the copper alloy / titanium alloy interface. It significantly improves the connection reliability and interface performance of bimetallic heterostructures.

[0017] In some embodiments, by sequentially machining, washing, first ultrasonic cleaning, drying, pickling, and second ultrasonic cleaning on the surfaces of the titanium alloy cylinder to be joined, a surface-activated titanium alloy cylinder is obtained. This process can synergistically remove oxide scale and oil stains, regulate microstructure, and thus enhance the wetting and diffusion bonding ability of the copper alloy / titanium alloy interface in subsequent steps, further suppressing the excessive formation of brittle intermetallic compounds.

[0018] In some embodiments, copper alloy powder is pre-treated by cold isostatic pressing to obtain pre-compacted copper alloy powder blocks, which are then placed into the inner hole of a surface-activated titanium alloy cylinder and pressed with a graphite indenter. This ensures that the pre-compacted copper alloy powder blocks have uniform density and regular shape before hot pressing and sintering, avoiding local current concentration and densification differences caused by uneven filling. This facilitates the stable reversal of the current path from along the periphery of the titanium alloy cylinder to through the densified copper alloy powder blocks, thereby improving the consistency of the copper alloy / titanium alloy connection interface.

[0019] In some embodiments, by controlling the median particle size of the copper alloy powder to be 45-70µm and the flowability to be 14-18s / 50g, and combining it with cold isostatic pressing pretreatment at 100-160MPa for 2-5min, a dense and uniform pre-compacted copper alloy powder block is obtained. A conical graphite indenter with a taper of 4-7° is used to convert the axial pressure into radial expansion extrusion force during hot pressing sintering, dynamically compensating for the shrinkage of the pre-compacted copper alloy powder block as it densifies, ensuring stable reversal of the current path, and suppressing pores and microcracks at the copper alloy / titanium alloy interface.

[0020] In some embodiments, a silver or nickel layer with a thickness of 10-20µm is electrodeposited on the inner hole of the surface to be joined of the surface-activated titanium alloy cylinder as an intermediate layer. Then, a pre-compacted copper alloy powder block and a graphite indenter are placed in sequence. The intermediate layer acts as a diffusion barrier during hot pressing and sintering, which can effectively suppress the formation of excessive brittle intermetallic compounds at the copper alloy / titanium alloy interface. At the same time, it improves the wettability of the copper alloy and titanium alloy, promotes the formation of a continuous and dense metallurgical bonding layer, and further enhances the bonding strength and reliability of the bimetallic heterostructure.

[0021] In some embodiments, by placing the assembly into a DC-assisted hot press furnace, the outer surface of the titanium alloy cylinder body, which is activated by the contact surface of the thermocouple temperature measuring end, is simultaneously subjected to mechanical pressure and DC current for hot pressing sintering under vacuum. This achieves real-time coordinated control of temperature, electric field, and force field, ensuring that the current path preferentially conducts along the periphery of the titanium alloy cylinder body. After the pre-compacted copper alloy powder is densified, the current automatically reverses. Combined with controlled cooling and furnace cooling, this effectively suppresses residual stress and microcracks at the copper alloy / titanium alloy connection interface, improving connection reliability.

[0022] In some embodiments, by controlling the pressure unloading rate to 1 MPa / min and the temperature after cooling to 300°C, the slow pressure release and step cooling of the assembly are achieved after hot pressing and sintering. This effectively avoids residual stress or microcracks at the bimetallic heterostructure interface caused by rapid pressure release and high-temperature furnace exit. At the same time, it suppresses the later precipitation and growth of brittle intermetallic compounds at the copper alloy / titanium alloy interface, ensuring that the pre-compacted copper alloy powder block after densification and the inner wall of the surface-activated titanium alloy cylinder maintain a stable and reliable metallurgical bonding state.

[0023] In some embodiments, a two-stage hot-pressing sintering process is employed: in the first stage, the temperature is raised to 500-550°C at a rate of 30-80°C / min and held at that temperature. The pre-compacted copper alloy powder blocks are used to conduct current along the outer periphery of the surface-activated titanium alloy cylinder body, thus preventing overheating of the inner hole. In the second stage, the temperature is raised to 650-700°C at a rate of 10-20°C / min and held under pressure. After the pre-compacted copper alloy powder blocks are densified, the current path automatically reverses to preferentially pass through the densified pre-compacted copper alloy powder blocks. This effectively suppresses the formation of excessive brittle intermetallic compounds and ensures that the cylinder body structure with a large aspect ratio and small inner hole remains undeformed.

[0024] In some embodiments, by controlling the hot pressing sintering pressure at 15-30 MPa, a stable axial mechanical pressure is provided for the inner wall of the pre-compacted copper alloy powder and the surface-activated titanium alloy cylinder. This ensures sufficient particle rearrangement and plastic deformation of the pre-compacted copper alloy powder during the densification process, while avoiding deformation of the titanium alloy cylinder due to excessive pressure. At the same time, the dynamic reversal of the current path from the periphery to preferentially passing through the densified pre-compacted copper alloy powder promotes tight bonding of the copper alloy / titanium alloy interface and suppresses pores and microcracks.

[0025] Secondly, this invention provides an electrically assisted bimetallic heterostructure for connecting copper alloy / titanium alloys. The densified, pre-compacted copper alloy powder and the surface-activated inner wall of the titanium alloy cylinder form a continuous and dense copper alloy / titanium alloy interface, effectively suppressing excessive brittle intermetallic compounds. Simultaneously, the titanium alloy cylinder remains undeformed, preserving its original microstructure and internal bore machining accuracy. It exhibits excellent bonding strength and shear resistance at the copper alloy / titanium alloy interface, making it suitable for cylinder structures with large aspect ratios and small inner bores. Attached Figure Description

[0026] Figure 1 This is a schematic diagram of the connection relationship in the method for preparing an electrically assisted copper / titanium alloy bimetallic heterostructure according to Embodiment 1 of the present invention. Figure 2 This is a schematic diagram of the connection relationship in the method for preparing the electrically assisted copper / titanium alloy bimetallic heterostructure as shown in Examples 2-3 of the present invention; Figure 3 This is a schematic diagram of the DC current path shown in Embodiments 1-3 of the present invention; Figure 4 This is a schematic diagram of the microstructure of the bimetallic heterostructure obtained in Example 1 of the present invention; Figure 5 This is a schematic diagram of the microstructure of the bimetallic heterostructure obtained in Example 2 of the present invention; Figure 6 This is a schematic diagram of the microstructure of the bimetallic heterostructure obtained in Example 3 of the present invention; Figure 7 This is a comparison diagram of the hardness of the copper alloy and titanium alloy in the bimetallic heterostructures obtained in Examples 1-3 of the present invention; Figure 8 This is a schematic diagram of the structure of the titanium alloy cylinder block shown in an embodiment of the present invention; In all the accompanying drawings, the same reference numerals denote the same technical features, specifically: 1. Negative electrode voltage probe; 2. Graphite insulation mold; 3. Cylindrical graphite pressure head; 4. Titanium alloy cylinder; 5. Thermocouple; 6. Copper alloy / titanium alloy interface; 7. Copper alloy powder; 8. Positive electrode voltage probe; 9. Conical graphite pressure head. Detailed Implementation

[0027] In the following description, only certain exemplary embodiments are briefly described. As those skilled in the art will recognize, the described embodiments can be modified in various ways without departing from the spirit or scope of the invention. Therefore, the drawings and description are considered to be exemplary in nature and not restrictive.

[0028] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this invention, "a plurality of" means two or more, unless otherwise explicitly specified.

[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0030] Copper / titanium alloy bimetallic materials effectively combine the electrical, thermal, and wear-resistant properties of copper with the high specific strength of titanium, thus demonstrating significant application value in aerospace, marine engineering, energy, and chemical industries. Taking aerospace hydraulic motor cylinder blocks as an example, current cylinder block materials mostly employ copper / alloy steel bimetallic structures. Replacing the alloy steel matrix with titanium alloys could effectively reduce weight by approximately 30%, thereby improving the overall maneuverability of the aircraft.

[0031] Currently, the fabrication of copper / titanium bimetallic alloys commonly employs bonding processes such as diffusion welding, electron beam welding, friction stir welding, explosive welding, laser welding, and hot isostatic pressing (HIP). However, these bonding processes have the following problems: First, aerospace hydraulic motor cylinders have complex porous structures with a depth-to-diameter ratio typically greater than 2:1, and some structural dimensions are small, with hole diameters ≤8mm. This places high demands on the bonding process, making it difficult to achieve reliable copper / titanium bimetallic bonding in structures like aerospace hydraulic motor cylinders using the aforementioned bonding processes. Second, the HIP process requires pre-filling the titanium alloy holes with copper alloy powder or copper alloy rods. If powder is used, pores are easily retained within the titanium alloy holes, causing deformation of the titanium alloy matrix during HIP and resulting in deviations in the hole diameter. If copper alloy rods are used instead, a complex sheathing structure needs to be designed, and the cylinder blank requires precise machining. Accurate positioning holes are used for subsequent positioning of the cylinder block hole center; in addition, hot isostatic pressing is a process of thermal radiation heating, and when the connection temperature is high, it will cause the titanium alloy to undergo a β phase transformation, thus affecting its material properties, while low connection temperatures make it difficult to achieve copper alloy / titanium alloy bimetallic connection; finally, the low solid solubility between copper alloy and titanium alloy makes it easy for various Cu-Ti brittle intermetallic compounds to form at the copper alloy / titanium alloy connection interface 6, which seriously weakens the mechanical properties of the copper alloy / titanium alloy connection interface 6. Especially during the liquid-solid phase connection process, the reaction at the copper alloy / titanium alloy connection interface 6 is violent, and various Cu-Ti brittle intermetallic compounds grow rapidly, which seriously deteriorates the performance of the copper alloy / titanium alloy connection interface 6.

[0032] This invention provides a method for preparing an electrically assisted copper / titanium alloy bimetallic heterostructure, comprising the following steps: Step 1: The pre-compacted copper alloy powder block and the graphite press head are sequentially placed into the inner hole of the surface-activated titanium alloy cylinder 4 to obtain the assembly. Step 2: The assembled components are hot-pressed and sintered using direct current to obtain a bimetallic heterostructure; wherein the current path of the direct current satisfies: The DC current path is first conducted along the periphery of the surface-activated titanium alloy cylinder 4. After the pre-compacted copper alloy powder is densified, the DC current path is reversed to preferentially pass through the densified pre-compacted copper alloy powder.

[0033] By controlling the direct current path to conduct along the periphery of the surface-activated titanium alloy cylinder 4, and utilizing the dynamic resistance changes of the pre-compacted copper alloy powder before and after densification, the current path automatically reverses after the pre-compacted copper alloy powder is densified, preferentially passing through the densified pre-compacted copper alloy powder, forming selective internal heat focusing. This can adapt to cylinder structures with large aspect ratios (>2:1) and small inner holes (≤8mm), preventing deformation of the titanium alloy cylinder 4 due to local overheating. Simultaneously, the current path conversion mechanism effectively suppresses the formation of excessive brittle intermetallic compounds at the copper alloy / titanium alloy interface 6, improving the bonding quality of the copper alloy / titanium alloy interface 6. Furthermore, by using a graphite indenter to achieve the synergistic effect of force and electric fields during the hot-pressing sintering process, the pre-compacted copper alloy powder is fully densified under low thermal load and forms a reliable metallurgical bond with the inner wall of the titanium alloy cylinder 4. This method solves the problems of existing technologies being difficult to adapt to cylinder structures with large depth-to-diameter ratios and small inner bores, which easily cause deformation of the titanium alloy cylinder 4, and the easy formation of excessive brittle intermetallic compounds at the copper alloy / titanium alloy connection interface 6. It significantly improves the connection reliability of the copper alloy / titanium alloy bimetallic heterostructure and the performance of the copper alloy / titanium alloy connection interface 6.

[0034] It should be noted that, for the sake of brevity, the room temperature in this invention is 25°C, and the specific room temperature will not be described separately in the following.

[0035] Example 1: This embodiment provides a method for preparing an electrically assisted bimetallic heterostructure connecting copper alloy / titanium alloy, including the following steps: Step 1: The pre-compacted copper alloy powder block and the graphite pressure head are sequentially placed into the inner hole of the surface-activated titanium alloy cylinder 4 to obtain the assembly.

[0036] Specifically, step 1 includes the following steps: Step 1.1: Machining all surfaces of the TC6 titanium alloy cylinder block to be joined to a surface roughness of Ra1.6μm, washing with gasoline to remove residual oil stains, then immersing in anhydrous ethanol for the first ultrasonic cleaning, and then drying in a drying oven. The dried TC6 titanium alloy cylinder block is then pickled to remove the surface oxide film. The pickled TC6 titanium alloy cylinder block is then immersed in anhydrous ethanol for a second ultrasonic cleaning to obtain a surface-activated TC6 titanium alloy cylinder block.

[0037] Step 1.2: Add WB2 ceramic particles with a median particle size of 5µm and a mass percentage of 5 wt.% to CuSn10 alloy powder with a median particle size of 70µm and a flowability of 14-15s / 50g. After vibrating and mixing for 8 hours, fill the mixture into a cylindrical isostatic pressing sleeve with a diameter of 7.8mm and a height of 18mm. The flowability of 14-15s / 50g is to ensure that the CuSn10 alloy powder can fully fill the space when loaded into the isostatic pressing sleeve, ensuring good contact between particles during the subsequent pre-compacting of the copper alloy powder block and hot pressing sintering, achieving uniform densification. Subsequently, control the pressure of the cold isostatic pressing pretreatment to 10. At 0 MPa and a pressurization rate of 18 MPa / min, the pressure is held for 2 min to obtain a pre-compacted copper alloy powder block with a certain strength. The pre-compacted copper alloy powder block is placed into the inner hole of the surface-activated TC6 titanium alloy cylinder to obtain a titanium alloy cylinder containing copper alloy powder. Then, a cylindrical graphite indenter 3 is pressed into the inner hole of the titanium alloy cylinder containing copper alloy powder. After pressing, the cylindrical graphite indenter 3 protrudes 10 mm above the end face of the surface-activated TC6 titanium alloy cylinder to obtain the assembly.

[0038] Step 2: The assembly is hot-pressed and sintered by direct current to obtain a bimetallic heterostructure; wherein the current path of the direct current satisfies the following: the current path of the direct current is first conducted along the periphery of the surface-activated titanium alloy cylinder 4, and after the pre-compacted copper alloy powder is densified, the current path of the direct current is reversed to preferentially pass through the densified pre-compacted copper alloy powder.

[0039] Specifically, step 2 includes the following steps: Step 2.1, see Figure 1 The assembly is placed into the graphite insulation mold 2 of the DC-assisted hot press furnace. Thermocouple 5 is passed through the graphite insulation mold 2, so that the temperature measuring end of thermocouple 5 directly contacts the outer surface of the surface-activated TC6 titanium alloy cylinder. The graphite insulation mold 2 is placed between the negative electrode voltage head 1 and the positive electrode voltage head 8 of the graphite electrode. Then, the vacuum degree of the DC-assisted hot press furnace is evacuated to ≤8.0×10. -3 The pressure was steadily increased to 30 MPa at a rate of 10 MPa / min, with the vacuum level ≤8.0 × 10⁻⁶ Pa. -3Pa is used to remove residual gas and moisture, reduce oxidation and porosity, and ensure good bonding at the copper alloy / titanium alloy interface 6. Then, DC current is turned on, controlling the output current to ≤5000A, to generate controllable Joule heating and directional electron flow. Resistance heating is used to activate the surface of the pre-compacted copper alloy powder and achieve early sintering. Simultaneously, at high temperatures, it promotes deep diffusion of elements at the copper alloy / titanium alloy interface 6, thereby optimizing the distribution of brittle intermetallic compounds. In the first stage, due to the high porosity and contact resistance of the pre-compacted copper alloy powder, the DC current preferentially conducts along the periphery of the surface-activated TC6 titanium alloy cylinder (dominated by series effect). Joule heating is used to raise the temperature to 500℃ at a rate of 80℃ / min and hold for 5min. This stage mainly achieves the activation of the surface of the pre-compacted copper alloy powder and the formation of a preliminary sintering neck.

[0040] Step 2.2: Continue heating at a rate of 20℃ / min to 650℃ and hold at that temperature and pressure for 5 minutes. In the second stage, as the cylindrical graphite indenter 3 continues to press down, the radial expansion extrusion force generated by the sidewall of the pre-compacted copper alloy powder dynamically compensates for the shrinkage of the pre-compacted copper alloy powder, achieving densification of the pre-compacted copper alloy powder. At the same time, the resistance of the central copper alloy region of the densified pre-compacted copper alloy powder drops sharply, the current path of the direct current reverses, and the high-density electron flow preferentially passes through the central copper alloy region of the densified pre-compacted copper alloy powder (parallel effect dominates). Through a strong electromigration effect, it promotes the deep diffusion of element 6 at the copper alloy / titanium alloy interface.

[0041] Step 2.3: After the heat preservation and pressure holding are completed, the temperature is slowly cooled to 300℃ at a cooling rate of 5℃ / min. Then, the pressure is slowly unloaded at a rate of 1MPa / min to release the residual thermal stress caused by the difference in thermal expansion coefficients at the copper alloy / titanium alloy interface 6. Finally, the furnace is cooled to room temperature to obtain a bimetallic heterostructure, namely a copper alloy / titanium alloy bimetallic cylinder.

[0042] See Figure 3 I represents the total current, I4 represents the current flowing through the titanium alloy cylinder 4, and I7 represents the current flowing through the central copper alloy region of the densified pre-compacted copper alloy powder block. 界面 This represents the current flowing through the copper alloy / titanium alloy interface 6. In the initial heating stage, due to the high porosity and interparticle contact resistance of the copper alloy powder 7, the overall resistance of the copper alloy region is higher than that of the surrounding titanium alloy region. Therefore, I preferentially forms a low-resistance conductive path along the titanium alloy cylinder 4, i.e., I4 dominates, thereby generating Joule heating through the titanium alloy region and achieving rapid and uniform overall heating. As the temperature rises and the copper alloy powder 7 gradually densifies, the contact between copper alloy particles strengthens, the overall resistance between copper alloy particles decreases significantly, and the current path gradually shifts towards the central copper alloy region, forming a path dominated by I7 and I... 界面The dominant conductivity mode, high-density electron flow forms a significant electromigration effect at the copper alloy / titanium alloy interface 6, which can promote the diffusion of Cu and Ti elements and the metallurgical bonding of the copper alloy / titanium alloy interface 6, and achieve selective internal thermal focusing of the copper alloy / titanium alloy interface 6, thereby obtaining a dense and high-strength copper alloy / titanium alloy interface 6 at a lower overall temperature.

[0043] In this embodiment, see Figure 4 At an observation scale of 5 μm, the copper alloy / titanium alloy interface 6 showed good bonding. The hardness of the copper alloy near the interface was 120 HV, and the hardness of the titanium alloy was 334 HV. Furthermore, the microstructure of the titanium alloy did not undergo significant phase transformation, and the microstructure of the copper alloy / titanium alloy interface 6 was free of defects such as cracks and voids.

[0044] Example 2: This embodiment provides a method for preparing an electrically assisted bimetallic heterostructure connecting copper alloy / titanium alloy, including the following steps: Step 1: The pre-compacted copper alloy powder block and the graphite pressure head are sequentially placed into the inner hole of the surface-activated titanium alloy cylinder 4 to obtain the assembly.

[0045] Specifically, step 1 includes the following steps: Step 1.1: Machining all surfaces of the TC4 titanium alloy cylinder block to be joined to a surface roughness of Ra0.8μm, washing with gasoline to remove residual oil stains, then immersing in anhydrous ethanol for the first ultrasonic cleaning, and then drying in a drying oven. The dried TC4 titanium alloy cylinder block is then pickled to remove the surface oxide film. The pickled TC4 titanium alloy cylinder block is then immersed in anhydrous ethanol for a second ultrasonic cleaning to obtain a surface-activated TC4 titanium alloy cylinder block.

[0046] Step 1.2: An electrodeposition process is used to prepare a 20µm thick nickel layer as an intermediate layer on the inner hole of the surface to be joined in the surface-activated TC4 titanium alloy cylinder body. This results in a titanium alloy cylinder body with an intermediate layer, used to prevent the violent reaction of copper and titanium elements. QAl10-5-5 copper alloy powder with a median particle size of 50µm and a flowability of 15-16s / 50g is filled into a conical isostatic pressing sleeve with a diameter of 7.8mm, a height of 18mm, and a taper of 7°. The flowability of 15-16s / 50g ensures that the QAl10-5-5 copper alloy powder is evenly distributed during the filling process, facilitating the bonding process. The subsequent pre-compacted copper alloy powder blocks and hot pressing sintering process achieve stable densification and good particle adhesion. Then, the pressure of the cold isostatic pressing pretreatment is controlled at 150 MPa, the pressurization rate is 17 MPa / min, and the pressure is held for 3 min to obtain pre-compacted copper alloy powder blocks with a certain strength. The pre-compacted copper alloy powder blocks are placed into the inner hole of the surface-activated TC4 titanium alloy cylinder to obtain a titanium alloy cylinder containing copper alloy powder blocks. Then, a conical graphite indenter 9 is pressed into the inner hole of the titanium alloy cylinder containing copper alloy powder blocks. After pressing, the conical graphite indenter 9 is 2 mm higher than the end face of the surface-activated TC4 titanium alloy cylinder to obtain the assembly.

[0047] Step 2: The assembly is hot-pressed and sintered by direct current to obtain a bimetallic heterostructure; wherein the current path of the direct current satisfies the following: the current path of the direct current is first conducted along the periphery of the surface-activated titanium alloy cylinder 4, and after the pre-compacted copper alloy powder is densified, the current path of the direct current is reversed to preferentially pass through the densified pre-compacted copper alloy powder.

[0048] Specifically, step 2 includes the following steps: Step 2.1, see Figure 2 The assembly is placed into the graphite insulation mold 2 of the DC-assisted hot press furnace. Thermocouple 5 is passed through the graphite insulation mold 2, so that the temperature measuring end of thermocouple 5 directly contacts the outer surface of the surface-activated TC4 titanium alloy cylinder. The graphite insulation mold 2 is placed between the negative electrode voltage head 1 and the positive electrode voltage head 8 of the graphite electrode. Then, the vacuum degree of the DC-assisted hot press furnace is evacuated to ≤7.6×10. -3 The pressure was steadily increased to 20 MPa at a rate of 10 MPa / min, with the vacuum level evacuated to ≤7.6 × 10⁻⁶. -3Pa is used to further suppress the oxidation reaction and porosity formation at the copper alloy / titanium alloy interface 6, ensuring uniform bonding at the interface. Then, direct current is turned on, controlling the output current to 3500-4000A, to promote deep diffusion of Cu and Ti elements through electromigration and control the growth of brittle intermetallic compounds. In the first stage, due to the high porosity and contact resistance of the pre-compacted copper alloy powder, the direct current preferentially conducts along the periphery of the surface-activated TC4 titanium alloy cylinder (dominated by series effect). Joule heating is used to raise the temperature to 550℃ at a rate of 60℃ / min and hold for 10min. This stage mainly achieves the activation of the surface of the pre-compacted copper alloy powder and the formation of a preliminary sintering neck.

[0049] Step 2.2: Continue heating to 700℃ at a rate of 15℃ / min, then hold at that temperature and pressure for 30min. In the second stage, as the conical graphite indenter 9 continues to press down, the radial expansion extrusion force generated by the sidewall of the pre-compacted copper alloy powder dynamically compensates for the shrinkage of the pre-compacted copper alloy powder, achieving densification of the pre-compacted copper alloy powder. At the same time, the resistance of the central copper alloy region of the densified pre-compacted copper alloy powder drops sharply, the current path of the direct current reverses, and the high-density electron flow preferentially passes through the central copper alloy region of the densified pre-compacted copper alloy powder (parallel effect dominates). Through a strong electromigration effect, it promotes the deep diffusion of element 6 at the copper alloy / titanium alloy interface.

[0050] Step 2.3: After the heat preservation and pressure holding are completed, the temperature is slowly cooled to 300℃ at a cooling rate of 5℃ / min. Then, the pressure is slowly unloaded at a rate of 1MPa / min to release the residual thermal stress caused by the difference in thermal expansion coefficients at the copper alloy / titanium alloy interface 6. Finally, the furnace is cooled to room temperature to obtain a bimetallic heterostructure, namely a copper alloy / titanium alloy bimetallic cylinder.

[0051] In this embodiment, see Figure 5 At an observation scale of 5 μm, the copper alloy / titanium alloy interface 6 showed good bonding. The hardness of the copper alloy near the interface was 180 HV, and the hardness of the titanium alloy was 328 HV. Furthermore, the microstructure of the titanium alloy did not undergo significant phase transformation, and the microstructure of the copper alloy / titanium alloy interface 6 was free of defects such as cracks and voids.

[0052] Example 3: This embodiment provides a method for preparing an electrically assisted bimetallic heterostructure connecting copper alloy / titanium alloy, including the following steps: Step 1: The pre-compacted copper alloy powder block and the graphite pressure head are sequentially placed into the inner hole of the surface-activated titanium alloy cylinder 4 to obtain the assembly.

[0053] Specifically, step 1 includes the following steps: Step 1.1: Machining all surfaces of the TC4 titanium alloy cylinder block to be joined to a surface roughness of Ra0.4μm, washing with gasoline to remove residual oil stains, then immersing in anhydrous ethanol for the first ultrasonic cleaning, and then drying in a drying oven. The dried TC4 titanium alloy cylinder block is then pickled to remove the surface oxide film. The pickled TC4 titanium alloy cylinder block is then immersed in anhydrous ethanol for a second ultrasonic cleaning to obtain a surface-activated TC4 titanium alloy cylinder block.

[0054] Step 1.2: Using an electrodeposition process, a 10µm thick silver layer is prepared on the inner hole of the surface to be joined in the surface-activated TC4 titanium alloy cylinder as an intermediate layer, resulting in a titanium alloy cylinder with an intermediate layer. This intermediate layer is used to prevent the violent reaction of copper and titanium elements. QAl10-5-5 copper alloy powder with a median particle size of 45µm and a flowability of 16.5-18s / 50g is filled into a conical isostatic pressing sleeve with a diameter of 7.8mm, a height of 18mm, and a taper of 4°. The flowability of 16.5-18s / 50g ensures that the QAl10-5-5 copper alloy powder is evenly distributed during the filling process. To achieve stable densification and good particle adhesion during the subsequent pre-compacted copper alloy powder block and hot pressing sintering process, the pressure of the cold isostatic pressing pretreatment is controlled at 160 MPa, the pressurization rate is 15 MPa / min, and the pressure is held for 5 min to obtain a pre-compacted copper alloy powder block with a certain strength. The pre-compacted copper alloy powder block is placed into the inner hole of the surface-activated TC4 titanium alloy cylinder to obtain a titanium alloy cylinder containing copper alloy powder block. Then, a conical graphite indenter 9 is pressed into the inner hole of the titanium alloy cylinder containing copper alloy powder block. After pressing, the conical graphite indenter 9 protrudes 5 mm above the end face of the surface-activated TC4 titanium alloy cylinder to obtain the assembly.

[0055] Step 2: The assembly is hot-pressed and sintered by direct current to obtain a bimetallic heterostructure; wherein the current path of the direct current satisfies the following: the current path of the direct current is first conducted along the periphery of the surface-activated titanium alloy cylinder 4, and after the pre-compacted copper alloy powder is densified, the current path of the direct current is reversed to preferentially pass through the densified pre-compacted copper alloy powder.

[0056] Specifically, step 2 includes the following steps: Step 2.1, see Figure 2 The assembly is placed into the graphite insulation mold 2 of the DC-assisted hot press furnace. Thermocouple 5 is passed through the graphite insulation mold 2, so that the temperature measuring end of thermocouple 5 directly contacts the outer surface of the surface-activated TC4 titanium alloy cylinder. The graphite insulation mold 2 is placed between the negative voltage head 1 and the positive voltage head 8 of the graphite electrode. Then, the vacuum degree of the DC-assisted hot press furnace is evacuated to ≤8.0×10. -3The pressure was steadily increased to 15 MPa at a rate of 10 MPa / min, with the vacuum level evacuated to ≤8.0 × 10⁻⁶ Pa. -3 Pa is used to effectively remove residual gas and moisture, preventing oxidation of the copper alloy / titanium alloy interface 6. Then, DC current is turned on, controlling the output current to 2000-2500A, to promote element diffusion through directional electron flow. In the first stage, due to the high porosity and contact resistance of the pre-compacted copper alloy powder, the DC current preferentially conducts along the periphery of the surface-activated TC4 titanium alloy cylinder (dominated by series effect). Joule heating is used to raise the temperature to 530℃ at a rate of 30℃ / min, and it is held for 8 minutes. This stage mainly achieves the activation of the surface of the pre-compacted copper alloy powder and the formation of the initial sintering neck.

[0057] Step 2.2: Continue heating at a rate of 10℃ / min to 650℃ and hold at that temperature and pressure for 5 minutes. In the second stage, as the conical graphite indenter 9 continues to press down, the radial expansion extrusion force generated by the sidewall of the pre-compacted copper alloy powder dynamically compensates for the shrinkage of the pre-compacted copper alloy powder, achieving densification of the pre-compacted copper alloy powder. At the same time, the resistance of the central copper alloy region of the densified pre-compacted copper alloy powder drops sharply, the current path of the direct current reverses, and the high-density electron flow preferentially passes through the central copper alloy region of the densified pre-compacted copper alloy powder (parallel effect dominates). Through a strong electromigration effect, it promotes the deep diffusion of element 6 at the copper alloy / titanium alloy interface.

[0058] Step 2.3: After the heat preservation and pressure holding are completed, the temperature is slowly cooled to 300℃ at a cooling rate of 5℃ / min. Then, the pressure is slowly unloaded at a rate of 1MPa / min to release the residual thermal stress caused by the difference in thermal expansion coefficients at the copper alloy / titanium alloy interface 6. Finally, the furnace is cooled to room temperature to obtain a bimetallic heterostructure, namely a copper alloy / titanium alloy bimetallic cylinder.

[0059] In this embodiment, see Figure 6 At an observation scale of 100 μm, the copper alloy / titanium alloy interface 6 showed good bonding. The hardness of the copper alloy near the interface was 115 HV, and the hardness of the titanium alloy was 332 HV. Furthermore, the microstructure of the titanium alloy did not undergo significant phase transformation, and the microstructure of the copper alloy / titanium alloy interface 6 was free of defects such as cracks and voids.

[0060] See Figure 7In Examples 1-3, the hardness of the titanium alloy side was 334 HV, 328 HV, and 332 HV, respectively, with relatively small overall changes. This indicates that the present invention effectively suppressed grain coarsening and β-phase transformation of the titanium alloy matrix during the joining process, preserving the original high-strength microstructure characteristics of the titanium alloy. In Examples 1-3, the hardness of the copper alloy side was 120 HV, 180 HV, and 115 HV, respectively. The copper alloy in Example 2 had the highest hardness, mainly due to the high strength of the QAl10-5-5 copper alloy powder itself. Simultaneously, the intermediate layer effectively suppressed the formation of Cu-Ti brittle intermetallic compounds, making the bonding of the copper alloy / titanium alloy interface 6 more stable. Therefore, the method for preparing the electrically assisted copper / titanium alloy bimetallic heterostructure proposed in this invention can achieve the bonding of copper and titanium alloys below the phase transformation temperature of the titanium alloy, while simultaneously considering the quality and microstructure stability of the copper / titanium alloy interface 6.

[0061] This invention assembles pre-compacted copper alloy powder blocks and a graphite pressure head. Utilizing the dynamic evolution of the resistance of the pre-compacted copper alloy powder blocks during densification, in the first stage (initial heating phase), the high contact resistance of the pre-compacted copper alloy powder blocks generates localized Joule heating in micro-areas, accelerating surface activation and early densification. In the second stage, near the holding temperature (650-700℃), after the pre-compacted copper alloy powder blocks have densified, the current path preferentially conducts along the periphery of the surface-activated titanium alloy cylinder 4, converging towards the central low-resistance copper alloy region. Through dynamic circuit switching, selective internal heat focusing on the copper alloy / titanium alloy interface 6 is achieved, significantly reducing the thermal load on the peripheral titanium alloy cylinder 4 while ensuring complete densification of the copper alloy powder 7.

[0062] This invention employs a cylindrical graphite indenter 3 or a conical graphite indenter 9, which can effectively convert axial pressure into radial expansion extrusion force during hot pressing sintering. This dynamically compensates for the volume shrinkage of the pre-compacted copper alloy powder during high-temperature solid-state sintering, ensuring that the copper alloy / titanium alloy interface 6 maintains extremely high adhesion throughout the entire thermo-coupling process. This effectively suppresses the initiation of pores and residual stress microcracks at the copper alloy / titanium alloy interface 6.

[0063] This invention utilizes direct current assistance to promote deep interdiffusion of elements at the copper / titanium alloy interface 6 during the high-temperature diffusion bonding stage. This is achieved through a high-density directional electron flow, optimizing the morphology and distribution of brittle intermetallic compounds at the interface, preventing excessive proliferation of brittle phases, significantly improving the fracture toughness and shear strength of the heterojunction, and preserving the matrix microstructure characteristics and macroscopic processing precision. Thanks to the synergistic control of the electric, thermal, and force fields, the bonding temperature is strictly controlled below the β-phase transformation temperature of the titanium alloy, fundamentally suppressing phase transformation and grain growth in the titanium alloy matrix, and preserving the high strength and toughness properties of the original material. See also... Figure 8 Due to the extremely small macroscopic thermal stress, the titanium alloy cylinder block 4 is not prone to thermal deformation, and the original inner hole precision is completely preserved, providing a reliable benchmark for subsequent precision machining and significantly reducing the overall manufacturing cost.

[0064] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or basic characteristics. Therefore, the embodiments should be considered exemplary and non-limiting in all respects.

[0065] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can be appropriately combined to form other embodiments that can be understood by those skilled in the art. The above content is only for illustrating the technical concept of the present invention and should not be used to limit the scope of protection of the present invention. Any modifications made to the technical solutions based on the technical concept proposed in this invention fall within the scope of protection of this invention.

Claims

1. A method for preparing an electrically assisted bimetallic heterostructure of copper alloy / titanium alloy, characterized in that, Includes the following steps: The pre-compacted copper alloy powder block and the graphite pressure head are sequentially placed into the inner hole of the surface-activated titanium alloy cylinder (4) to obtain the assembly; The assembled components are hot-pressed and sintered using direct current to obtain a bimetallic heterostructure; wherein the current path of the direct current satisfies: The DC current path is first conducted along the periphery of the surface-activated titanium alloy cylinder (4). After the pre-compacted copper alloy powder is densified, the DC current path is reversed to preferentially pass through the densified pre-compacted copper alloy powder.

2. The method for preparing an electrically assisted copper / titanium alloy bimetallic heterostructure according to claim 1, wherein the preparation step of the surface-activated titanium alloy cylinder (4) specifically includes: The surfaces of the titanium alloy cylinder (4) to be connected are sequentially machined, washed, subjected to first ultrasonic cleaning, dried, pickled and subjected to second ultrasonic cleaning to obtain a surface-activated titanium alloy cylinder (4). After machining, the surface roughness of the titanium alloy cylinder block (4) to be connected is Ra 0.4-1.6 μm.

3. The method for preparing an electrically assisted copper alloy / titanium alloy bimetallic heterostructure according to claim 1, wherein the step of sequentially placing the pre-compacted copper alloy powder block and the graphite indenter into the inner hole of the surface-activated titanium alloy cylinder (4) to obtain the assembly, specifically includes: Copper alloy powder (7) is filled into an isostatic pressing sleeve for cold isostatic pressing pretreatment to obtain pre-compacted copper alloy powder blocks. The pre-compacted copper alloy powder blocks are placed into the inner hole of a surface-activated titanium alloy cylinder (4) to obtain a titanium alloy cylinder containing copper alloy powder blocks. A graphite press head is pressed into the inner hole of the titanium alloy cylinder containing copper alloy powder blocks to obtain an assembly.

4. The method for preparing an electrically assisted copper / titanium alloy bimetallic heterostructure according to claim 3, wherein the median particle size of the copper alloy powder (7) is 45-70µm and the flowability of the copper alloy powder (7) is 14-18s / 50g; The pressure of the cold isostatic pressing pretreatment is 100-160MPa, and the holding time of the cold isostatic pressing pretreatment is 2-5min; The graphite indenter is a cylindrical graphite indenter (3) or a conical graphite indenter (9), and the taper of the conical graphite indenter (9) is 4-7°.

5. The method for preparing an electrically assisted copper alloy / titanium alloy bimetallic heterostructure according to claim 1, wherein the step of sequentially placing a pre-compacted copper alloy powder block and a graphite indenter into the inner hole of a surface-activated titanium alloy cylinder (4) to obtain an assembly, specifically includes: An intermediate layer was prepared on the inner hole of the surface to be connected in the surface-activated titanium alloy cylinder (4) by electrodeposition process, and a titanium alloy cylinder with an intermediate layer was obtained. The pre-compacted copper alloy powder block and the graphite pressure head are sequentially placed into the inner hole of the titanium alloy cylinder with the intermediate layer to obtain the assembly. The thickness of the intermediate layer is 10-20µm, and the intermediate layer is a silver layer or a nickel layer.

6. The method for preparing an electrically assisted copper / titanium alloy bimetallic heterostructure according to claim 1, wherein the hot-pressing sintering of the assembly by direct current specifically includes: The assembly is placed in a DC-assisted hot press furnace, so that the temperature measuring end of the thermocouple (5) contacts the outer surface of the surface-activated titanium alloy cylinder (4). Then, mechanical pressure is applied under vacuum, and DC power is turned on for hot pressing sintering. Then, cooling, pressure unloading and furnace cooling are performed in sequence.

7. The method for preparing an electrically assisted copper / titanium alloy bimetallic heterostructure according to claim 6, wherein the temperature after cooling is 300°C and the pressure unloading rate is 1 MPa / min.

8. The method for preparing an electrically assisted copper / titanium alloy bimetallic heterostructure according to claim 1, wherein the hot pressing sintering comprises a first stage and a second stage performed sequentially; The first stage includes: Using pre-compacted copper alloy powder blocks, the DC current is conducted along the periphery of the surface-activated titanium alloy cylinder (4), and the temperature is raised to 500-550℃ at a rate of 30-80℃ / min and then held for 5-10 min. The second stage includes: heating to 650-700℃ at a rate of 10-20℃ / min and holding at that temperature and pressure for 5-30 minutes. After the pre-compacted copper alloy powder is densified, the current path of the DC power is reversed to preferentially pass through the densified pre-compacted copper alloy powder.

9. The method for preparing an electrically assisted copper / titanium alloy bimetallic heterostructure according to claim 1, wherein the hot pressing sintering pressure is 15-30 MPa.

10. A bimetallic heterostructure for electrically assisted connection of copper alloy / titanium alloy, characterized in that, It is obtained by the method for preparing an electrically assisted copper / titanium alloy bimetallic heterostructure according to any one of claims 1-9.